DEVELOPMENT OF RURAL AREA BY RENEWABLE ENERGY USING BIOGAS PLANT - Bangi Arifa K; Itkar Omshri D; Byagalli Viresh R; M. R. Jadhav (International Engineering Journal For Research & Development, 2020)
Renewable energy, often referred to as clean energy, comes from natural sources or processes that are constantly replenished. For example, sunlight or wind keep shining and blowing, even if their availability depends on time and weather. While renewable energy is often thought of as a new technology, harnessing nature’s power has long been used for heating, transportation, lighting, and more. Wind has powered boats to sail the seas and windmills to grind grain. The sun has provided warmth during the day and helped kindle fires to last into the evening. But over the past 500 years or so, humans increasingly turned to cheaper, dirtier energy sources such as coal and frocked gas.